2022
DOI: 10.3389/fnins.2022.1030230
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion kurtosis imaging and diffusion tensor imaging parameters applied to white matter and gray matter of patients with anti-N-methyl-D-aspartate receptor encephalitis

Abstract: ObjectivesTo compare parameters of diffusion tensor imaging (DTI) and diffusion kurtosis imaging (DKI) to evaluate which can better describe the microstructural changes of anti-N-methyl-D-aspartate receptor (NMDAR) encephalitis patients and to characterize the non-Gaussian diffusion patterns of the whole brain and their correlation with neuropsychological impairments in these patients.Materials and methodsDTI and DKI parameters were measured in 57 patients with anti-NMDAR encephalitis and 42 healthy controls. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…In DKI model, MK value reflects the complexity and structural integrity of brain tissue ( Das et al, 2017 ). Previous studies on the application of DKI to low-grade gliomas ( Goryawala et al, 2018 ) and inflammation ( Liu et al, 2022 ) have demonstrated lower radial kurtosis (RK) values in lesions in comparison to healthy controls or contralateral normal-appearing white matter, which related to the destructive impact exerted by tumor cells or inflammation on brain tissue. In our research, the values of MK in glioma were lower, suggesting more severe structural damage in glioma than inflammatory lesions.…”
Section: Discussionmentioning
confidence: 99%
“…In DKI model, MK value reflects the complexity and structural integrity of brain tissue ( Das et al, 2017 ). Previous studies on the application of DKI to low-grade gliomas ( Goryawala et al, 2018 ) and inflammation ( Liu et al, 2022 ) have demonstrated lower radial kurtosis (RK) values in lesions in comparison to healthy controls or contralateral normal-appearing white matter, which related to the destructive impact exerted by tumor cells or inflammation on brain tissue. In our research, the values of MK in glioma were lower, suggesting more severe structural damage in glioma than inflammatory lesions.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, extensive white matter damage assessed by diffusion tensor imaging related to disease severity and cognitive impairment has been previously reported in NMDAR encephalitis patients [ 6 , 48 50 ]. Moreover, a recent diffusion kurtosis imaging study also reported extensive gray matter microstructural damage in patients with NMDAR encephalitis [ 51 ]. Together, these studies indicate brain-wide dysfunction of NMDA receptors, with predominant alteration of hippocampal function.…”
Section: Discussionmentioning
confidence: 99%
“…However, brain structural and functional abnormalities in NMDAR encephalitis seems to extend beyond hippocampus. A number of recent works using different MR techniques as DTI, diffusion kurtosis imaging, voxel-based morphometry (VBM) and surface-based morphometry disclosed diffuse structural changes in hemispheric WM and cortical and subcortical GM, with correlation with cognitive scores ( Table 3 ) [ 117 , 118 , 119 , 120 , 121 ]. Accordingly, network analysis of resting-state fMRI data in patients with post-acute NMDAR encephalitis revealed alterations in whole-brain functional connectivity including impairment of the connectivity between the hippocampus and the medial temporal lobe (MTL) and the DMN, and significant reductions in intranetwork connectivity within the MTL, sensorimotor, lateral-temporal, and visual networks [ 122 ].…”
Section: Secondary Neurodegeneration In Patients With Autoimmune Ence...mentioning
confidence: 99%